Patrinia scabiosaefolia L. Modulates the Intestinal Microecology to Treat DSS-Induced Ulcerative Colitis: UHPLC-OE-MS/MS, Network Pharmacology, and Experimental Validation - Longfei Zhang; Xiaoxiao Liu; Mingze Xu; Xinyi Cheng; Ning Li; Haiyan Xu; Yining Feng; Tianzhu Guan; Lixia Xiao (Foods)
Patrinia scabiosaefolia L. (P. scabiosaefolia), a traditional food and medicinal plant, is used to treat internal inflammation. This study investigated the mechanisms by which P. scabiosaefolia improves ulcerative colitis (UC) via combined UHPLC-OE-MS/MS, network pharmacology, molecular docking, and animal experiments. A total of 72 compounds were detected in the P. scabiosaefolia extraction, with 15 key components (ranking by degree value) selected for further analysis. GO enrichment analysis suggested that PS may alleviate UC-related renal dysfunction by modulating immune responses, inflammation, and cell signaling pathways. Based on protein–protein interaction results, five core targets of P. scabiosaefolia in UC (ranking by degree value) were identified, and molecular docking revealed strong binding free affinity (<−7 kcal/mol) of active components (Vulgarin and 4-(Diphenylphosphino)benzoic acid) with TNF, AKT1, CASP3, BCL2, and MMP9. In animal experiments, P. scabiosaefolia-treated mice showed significant reductions in IL-6, TNF-α, LPS, and D-Lactate levels (p < 0.05); improved colon histopathological damage; and significantly increased the mRNA expression of tight junction proteins (ZO-1, Claudin, OCC) in colon tissue (p < 0.05). Furthermore, P. scabiosaefolia-treated mice exhibited a significant increase in beneficial gut bacteria (Enterococcus and Lactobacillus) (p < 0.05), effectively restoring the gut imbalance caused by DSS. In conclusion, P. scabiosaefolia can treat UC through the modulation of the intestinal microecology.